Short Time Perturbation Solution for Thermoelastic Instabilities in Planar Solidification - Yigit, Faruk (TRANS TECH PUBLICATIONS LTD, 2012)
A simplified thermomechanical growth instability model for early stages of solidification porcess is obtained. The model consists of a thermally deformable mold of finite thickness. The inclusion of the mold into the model introduces a parameter known as distortivity which plays an important role in the thermoelastic instability problems. The results show that the perturbation in contact pressure tends asymptotically to a maximum value at larger values of time. The magnitude of the contact pressure perturbation decreases as the thickness of the mold increases whereas it increases as the distortivity of the mold increases.
Keywords: Perturbation; Thermoelastic; Instability; Solidification; Engineering; Materials Science